The Effect of the Using “Spirit Fingers” Story from the Webtoon Application to Improve Students’ Vocabulary Mastery at SMA N 2 Sungai Limau - Rahmadhani, Annisa; Kher, Dinovia Fannil (Universitas Negeri Padang, 2024)
The research aims to identify the effect of using Spirit Fingers from Webtoon application in improving students’ vocabulary mastery in eleventh-grade students. This research was a pre-experimental research design. The population of the study was Eleventh-grade students at SMA N 2 Sungai Limau. The population consists of 204 students who are classified into six classes. XI FASE F3 was selected as a sample through the cluster random sampling method. The total number of students in this class was 33 students. The research was conducted in seven meetings. The researcher used pre-tests and post-tests to collect the data. The instrument of this research was a vocabulary test. There were 37 multiple-choice questions. The result of the study shows that the significant value of the two-tailed paired sample t-test was less than 0.05. This means that this research’s null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. It proved that using the Spirit Fingers story from the Webtoon application significantly improved students' vocabulary mastery at SMA N 2 Sungai Limau.